Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.5812/jjm.43213
|View full text |Cite
|
Sign up to set email alerts
|

The Frequency and Typing of Human Papilloma Virus Among Women with Normal and Abnormal Cytology in Southern Khorasan, Eastern Iran

Abstract: Background: Infection by certain types of human papilloma virus (HPV) is known as a causal and essential factor for cervical cancer, the second most common malignancy in women around the world.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…A list of included studies is shown in Table 1. The HPV prevalence and genotypes were investigated in 10,081 women with normal cervical cytology, 19–34 there were 158 women with atypical squamous cells of undetermined significance (ASCUS) or atypia, 27,32,34–37 360 women with low‐grade squamous intraepithelial lesion (LSIL) or cervical intraepithelial neoplasia I (CIN I), 27,32,34–42 183 women with high‐grade squamous intraepithelial lesion (HSIL) or CIN II‐III, 32,35–40,43 and 1111 women with invasive cervical cancer (ICC) 19,23,29,32,35–40,44–50 . As indicated in Table 2, the overall HPV prevalence was found to be 9% (CI = 6–14) in women with a normal cervix, 55% (CI = 34–75) in ASCUS (atypia) cases, 58% (CI = 43–73) in women with LSIL (CIN I), 69% (CI = 52–82) in HSIL (CIN II‐III) cases, and 81% (CI = 71–88) among women with ICC (Figures 2–3).…”
Section: Resultsmentioning
confidence: 99%
“…A list of included studies is shown in Table 1. The HPV prevalence and genotypes were investigated in 10,081 women with normal cervical cytology, 19–34 there were 158 women with atypical squamous cells of undetermined significance (ASCUS) or atypia, 27,32,34–37 360 women with low‐grade squamous intraepithelial lesion (LSIL) or cervical intraepithelial neoplasia I (CIN I), 27,32,34–42 183 women with high‐grade squamous intraepithelial lesion (HSIL) or CIN II‐III, 32,35–40,43 and 1111 women with invasive cervical cancer (ICC) 19,23,29,32,35–40,44–50 . As indicated in Table 2, the overall HPV prevalence was found to be 9% (CI = 6–14) in women with a normal cervix, 55% (CI = 34–75) in ASCUS (atypia) cases, 58% (CI = 43–73) in women with LSIL (CIN I), 69% (CI = 52–82) in HSIL (CIN II‐III) cases, and 81% (CI = 71–88) among women with ICC (Figures 2–3).…”
Section: Resultsmentioning
confidence: 99%
“…Studies related to the prevalence of HPV in Iranian women have estimated the prevalence of the virus in different provinces to be 5.5%–36. 5% [ 18 24 ]. The virus has been reported to be more prevalent in women with sexually transmitted infections and cervical cancer, as well as in women with high-risk behaviors [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…HPV DNA was detected by using the nested-PCR (nPCR) method. The universal primers MY09/11 (outer) and GP5+/6+ (inner) were used for L1 amplification and the detection of HPV-positive specimens according to previous protocols (5,6). The Bio-Rad T100™ Thermal cycler was used for the polymerase chain reaction.…”
Section: Hpv Detectionmentioning
confidence: 99%
“…The Bio-Rad T100™ Thermal cycler was used for the polymerase chain reaction. Furthermore, Beta globin as an external PCR control was used following the previous protocols (5,6). The heating program was as follows: 1st at 95°C for 5min, 45st at 95°C for 30 s, 56°C for 30 s (for outer primers), 48°C for 30 s (for inner primers), 72°C for 45 s, and 1st at 72°C for 5 min.…”
Section: Hpv Detectionmentioning
confidence: 99%